232k views
5 votes
Help me out please and thank you

Help me out please and thank you-example-1

1 Answer

2 votes

Answer: 1

========================================================

Step-by-step explanation:

We're given the height in relation to base BC, so we need to find the length of this base. This is the same as finding the distance from B to C.

Turn to the distance formula


d = \text{Distance from B to C}\\\\d = √((x_1-x_2)^2+(y_1-y^2)^2)\\\\d = √((-2-(-3))^2+(-1-(-2))^2)\\\\d = √((-2+3)^2+(-1+2)^2)\\\\d = √((1)^2+(1)^2)\\\\d = √(1+1)\\\\d = √(2)\\\\

Coincidentally, the base and height are the same. This won't always be the case.

Now we can find the area of the triangle


A = \text{Area of triangle}\\\\A = (1)/(2)*\text{Base}*\text{Height}\\\\A = (1)/(2)*√(2)*√(2)\\\\A = (1)/(2)*√(2*2)\\\\A = (1)/(2)*√(4)\\\\A = (1)/(2)*2\\\\A = 1\\\\

The area of the triangle is 1 square unit.

See diagram below.

Help me out please and thank you-example-1
User Morcutt
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.